2021
DOI: 10.1016/j.jallcom.2020.156671
|View full text |Cite
|
Sign up to set email alerts
|

Bio-synthesised black α-Cr2O3 nanoparticles; experimental analysis and density function theory calculations

Abstract: A selective single phase black a-Cr 2 O 3 nanoparticles was bio-synthesised via simple straight-forward green synthesis approach. The process involves extraction of phytochemicals contained in peels of sweet potatoes. Extraction was done in distilled water under constant magnetic stirring at a temperature of 70e80 C resulting in a dusty yellow colour aqueous extracts. Afterwards, chromic nitrate salt was added to extracts resulting in reduction of metal salt to metal nanoparticles. Obtained precipitates were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 52 publications
0
7
1
Order By: Relevance
“…The absorption band in the UV region is attributed to phytomolecules such as polyphenols and flavonoids, and these molecules absorb UV light because of the OH moieties [ 13 , 24 , 25 ]. The absorption band in the visible region corresponds to Cr 2 O 3 [ 26 , 27 , 28 , 29 ]. Moreover, the plant leaf extracts presented the UV region’s absorption band (200–390 nm) [ 10 ].…”
Section: Resultsmentioning
confidence: 99%
“…The absorption band in the UV region is attributed to phytomolecules such as polyphenols and flavonoids, and these molecules absorb UV light because of the OH moieties [ 13 , 24 , 25 ]. The absorption band in the visible region corresponds to Cr 2 O 3 [ 26 , 27 , 28 , 29 ]. Moreover, the plant leaf extracts presented the UV region’s absorption band (200–390 nm) [ 10 ].…”
Section: Resultsmentioning
confidence: 99%
“…A linear increase in the magnetism of Cr 2 O 3 nanoparticles with the field strength was found, which was suggested to be due to the presence of uncompensated spins at the nanoparticles' surface, leading to a nonmagnetic or antiferromagnetic state. e structural, electronic, and magnetic characteristics of Cr 2 O 3 were further confirmed using density functional theory (DFT) [157].…”
Section: Chromium and Chromium Oxide (Cr And Cr 2 O 3 )mentioning
confidence: 91%
“…1) with some notable interesting properties. From several reports, [9][10][11][12][13][14][15][16][17][18][19] we found that the different processed Cr 2 O 3 nanomaterials have revealed quite interesting results on the structural features related to phase formation, purity, lattice parameters, crystalline size, and so on. The green synthesized Cr 2 O 3 nanomaterials reported by Hassan et al 19 and Sackey et al 12 showed quite similar structural parameters of a = 0.495876 nm and c = 1.35942 nm 19 and a = 0.495 nm and c = 1.3591 nm, 12 respectively.…”
mentioning
confidence: 88%
“…From several reports, [9][10][11][12][13][14][15][16][17][18][19] we found that the different processed Cr 2 O 3 nanomaterials have revealed quite interesting results on the structural features related to phase formation, purity, lattice parameters, crystalline size, and so on. The green synthesized Cr 2 O 3 nanomaterials reported by Hassan et al 19 and Sackey et al 12 showed quite similar structural parameters of a = 0.495876 nm and c = 1.35942 nm 19 and a = 0.495 nm and c = 1.3591 nm, 12 respectively. It has been mentioned in Sangeetha et al 11 article that in cement and in lime bonded construction materials, Cr 2 O 3 nanomaterials are used not only as the permanent coloring agent but also it can be used in surface coating applications.…”
mentioning
confidence: 88%